Identifikasi dan Virulensi Fusarium oxysporum f.sp. cubense RAS 4 - Dwi Kiswanti; Suryanti Suryanti; Christanti Sumardiyono (Universitas Gadjah Mada, 2010)
The aim of this study was to identify and to detect the virulence of Fusarium oxysporum f.sp. cubense (Foc) race 4. The isolates consisted of BNT-2, KD-1, U-8, BK, A-2, and A-13. Monospore isolation was done to obtain stable isolates. The detection and characteristics of isolates were observed on Komada medium. The diameter of colony and color was observed from underside of culture in petridish, while the shape of colony was observed from the upper side. Virulence test was conducted on Cavendish cultivar seedlings. Banana seedlings were inoculated with Foc cultured on rice medium (20 g/kg soil). The result indicated that A-13, U-8, BNT-2, and BK, were very virulent isolates; while A-2 and KD-1 were virulent. All isolates were detected as Foc race 4, with mild yellowish color and laccinated colonies on Komada medium.